2023
DOI: 10.1021/acsaelm.3c00922
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Schottky Barrier and Efficient Ohmic Contacts in MSi2N4 (M = Mo, W)/2D Metal Contacts

Wen Ai,
Yongfei Shi,
Xiaohui Hu
et al.

Abstract: Monolayer MSi2N4 (M = Mo, W) has been fabricated and proposed as a promising channel material for field-effect transistors (FETs) due to the high electron/hole mobility. However, the barrier between the metal electrode and MSi2N4 will affect device performance. Hence, it is desirable to reduce the barrier for achieving high-performance electrical devices. Here, using density functional theory (DFT) calculations, we systematically investigate the electrical properties of the van der Waals (vdW) contacts formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…Previous studies have reported a Schottky to Ohmic contact transition in MS heterojunctions by applying several techniques such as electric field, doping, interlayer distance, altering the metal work function and strain engineering, thus achieving a tunneling probability of 100% by reducing the barrier width ( d TB ) to 0 eV . This Schottky to Ohmic transition has also been previously observed in graphene/MoSi 2 X 4 (X = N, P, and As) and MSi 2 N 4 /2D metal (M = Mo and W) vdW heterostructures. Based on these reports, applying electric field, strain engineering, and varying interlayer distance may tune the electric contact properties in studied heterostructures resulting in enhanced efficiency of nanoelectronic devices.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Previous studies have reported a Schottky to Ohmic contact transition in MS heterojunctions by applying several techniques such as electric field, doping, interlayer distance, altering the metal work function and strain engineering, thus achieving a tunneling probability of 100% by reducing the barrier width ( d TB ) to 0 eV . This Schottky to Ohmic transition has also been previously observed in graphene/MoSi 2 X 4 (X = N, P, and As) and MSi 2 N 4 /2D metal (M = Mo and W) vdW heterostructures. Based on these reports, applying electric field, strain engineering, and varying interlayer distance may tune the electric contact properties in studied heterostructures resulting in enhanced efficiency of nanoelectronic devices.…”
Section: Resultssupporting
confidence: 63%
“…Based on these reports, applying electric field, strain engineering, and varying interlayer distance may tune the electric contact properties in studied heterostructures resulting in enhanced efficiency of nanoelectronic devices. Addressing the shift from Schottky to Ohmic contacts in these MS heterostructures can help regulate interfacial current flow and improve carrier transport probability for a variety of electronic applications. , …”
Section: Resultsmentioning
confidence: 99%
“…Two-dimensional (2D) semiconductors, such as graphene, transition metal dichalcogenides (TMDs), and black phosphorene (BP), have exhibited potential applications in field effect transistors (FETs). However, their practical applications still have some limitations, such as the zero-band gap in graphene, , poor environmental stability in BP, , and low carrier mobility in TMDs. , MoSi 2 N 4 and WSi 2 N 4 monolayers, recently synthesized by the chemical vapor deposition (CVD), have shown the potential to realize high-speed and low-power consumption devices due to the suitable band gap, high carrier mobility, and outstanding environmental stability. Another MoSi 2 N 4 family material, the MoGe 2 P 4 monolayer, has attracted much attention due to its suitable band gap (0.5 eV) and outstanding carrier mobility (exceeding 10 3 cm 2 V –1 s –1 ), which is higher than those of the recently reported MoSi 2 N 4 /WSi 2 N 4 . Besides, the MoGe 2 P 4 monolayer is both dynamically and mechanically stable, which is much better than that of black phosphorene .…”
Section: Introductionmentioning
confidence: 99%